2015
DOI: 10.1097/aln.0000000000000551
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Core Temperature Patterns, Transfusion Requirement, and Hospital Duration in Patients Warmed with Forced Air

Abstract: Background Core temperature patterns in patients warmed with forced-air remain poorly characterized. Also unknown is the extent to which transient and mild intraoperative hypothermia contributes to adverse outcomes in broad populations. Methods We evaluated esophageal (core) temperatures in 58,814 adults having surgery lasting >60 min who were warmed with forced air. Independent associations between hypothermic exposure and transfusion requirement and duration of hospitalization was evaluated. Results In e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
102
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(117 citation statements)
references
References 39 publications
(43 reference statements)
6
102
1
Order By: Relevance
“…Likewise, the US Institute for Healthcare Improvement suggests the use of active methods to maintain normothermia in surgical patients . However, even when active warming techniques are used, perioperative hypothermia is common . This meta‐analysis demonstrates a benefit with the use of warmed, humidified CO 2 , with an overall effect size of +0.3°C.…”
Section: Discussionmentioning
confidence: 83%
“…Likewise, the US Institute for Healthcare Improvement suggests the use of active methods to maintain normothermia in surgical patients . However, even when active warming techniques are used, perioperative hypothermia is common . This meta‐analysis demonstrates a benefit with the use of warmed, humidified CO 2 , with an overall effect size of +0.3°C.…”
Section: Discussionmentioning
confidence: 83%
“…1), which is likely to be of higher importance than the mere determination of core temperature at suture time [1]. 1), which is likely to be of higher importance than the mere determination of core temperature at suture time [1].…”
Section: Discussionmentioning
confidence: 99%
“…Peri-operative hypothermia is recognised to be an independent risk factor for wound infections, blood transfusions, cardiovascular events and increased peri-operative morbidity and mortality [1]. This was illustrated at our Centre for Abdominal Surgery where analysis of 20 patients undergoing pylorus-preserving pancreatic head resection (PPPR) between June 2015 to May 2016 showed that the mean body core temperature at the end of the procedure was 35.1 ± 0.7°C (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…The patient's experience of surgery may also be affected by PIH as thermal comfort can impact overall perceptions of care (Fossum, Hays, & Henson, ; Kolcaba & Wilson, ; Wagner, Byrne, & Kolcaba, ). Complications associated with PIH can lead to prolonged postoperative recovery, poorer patient experience, prolonged length of stay, increased resourcing requirements and higher healthcare‐related costs (Billeter, Hohmann, Druen, Cannon, & Polk, ; Nieh & Su, ; Sun et al., ).…”
Section: Introductionmentioning
confidence: 99%